Verbal and Visual Signs on Apple Advertisement Video Entitled "Privacy on iPhone" - Gusti Ayu Putu Agung Silvia Sari; Ni Wayan Sukarini; Sang Ayu Isnu Maharani (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2026)
This research entitled Verbal and Visual Signs on Apple Advertisement Video Entitled “Privacy on iPhone”. This research focuses on the analysis of the verbal and visual signs and the meaning intended in video scenes. This research aims at finding and analysing the meaning of the verbal and visual signs (signifiers) used in the advertisement video. The data were taken from Apple Advertisement Video entitled “Privacy on iPhone”. This research was using qualitative method. The documentation method and note-taking technique were applied in collecting the data. The data were analyzed by applying the descriptive and qualitative method. To present data analysis by using images of the scenes, tables and explained descriptively. Theory of Semiotics proposed by Saussure, theory of Verbal and Visual Sign from Dyer, and theory of Meaning by Leech were used to analyze the data. The result of this research shows that there are 4 scenes with total 30 images appeared chronologically in the video containing verbal and visual signs (signifiers). The verbal signs found are spoken and written aspect. The visual signs found are appearance, manner, activity, props and setting, and the analyzing photograph. This advertisement has connotative and denotative meanings. Keywords: Advertisement Video, Verbal Signs, Visual Signs